Health Omnibus Law: Perspective of Legal Sociology - Tauchid Noor; Sutarno; Huda, Mokhamad Khoirul (Technium Social Sciences Journal, 2025)
Law Number 17 of 2023 concerning Health has adopted the use of the omnibus law method. It is necessary to study in depth how the formation process must be in accordance with the law on the formation of laws and regulations. Because it combines almost 9 existing laws, from a sociological perspective, law has a very large influence in the formation process. Strategic issues in the formation of the health law are related to authority, institutions, organizations, professional education issues, competency tests, interventions to the administrative field. For this reason, in the implementation and evaluation stages, the sustainability of the law needs to be carried out so that the purpose of the birth of the omnibuslaw method of forming health laws can be achieved for the benefit of all parties. Law Number 17 of 2023 concerning Health has adopted the use of the omnibus law method. It is necessary to study in depth how the formation process must be in accordance with the law on the formation of laws and regulations. Because it combines almost 9 existing laws, from a sociological perspective, law has a very large influence in the formation process. Strategic issues in the formation of the health law are related to authority, institutions, organizations, professional education issues, competency tests, interventions to the administrative field. For this reason, in the implementation and evaluation stages, the sustainability of the law needs to be carried out so that the purpose of the birth of the omnibuslaw method of forming health laws can be achieved for the benefit of all parties.